Microalgae and cyanobacteria as a tool for agricultural sustainability: a review of biofertilizer and biostimulant potential - Sun, Zhongliang; Liu, Xiaoyan; Ugya, Adamu Yunusa; Liu, Haiyan; Sun, Liqin; Luo, Guanghong (Frontiers in Plant Science, 2026)
Microalgae and cyanobacteria are emerging as sustainable alternatives to chemical fertilizers and pesticides, offering nutrient recycling, stress mitigation, and environmental restoration within the framework of circular bioeconomy. This review synthesizes recent advances in the utilization of cyanobacteria and green microalgae as biofertilizers, biostimulants, and biopesticides, emphasizing their physiological mechanisms and agronomic potential. Microalgae and cyanobacteria can fix atmospheric nitrogen, solubilize phosphorus, and supply essential micronutrients through exopolysaccharides, organic acids, and siderophores, thereby improving soil fertility and structure. Their metabolites, including phytohormones, amino acids, and antioxidants, stimulate seed germination, root growth, nutrient uptake, and tolerance to abiotic stresses such as drought and salinity. Moreover, allelochemicals and antimicrobial compounds from microalgae can suppress plant pathogens and reduce pesticide dependence. Integrating microalgae cultivation with wastewater and flue gas utilization promotes nutrient recycling and CO2 sequestration, further enhancing environmental sustainability. However, large-scale application remains limited by biomass production costs, inconsistent performance under field conditions, and regulatory uncertainty. Overall, microalgae-based fertilizers and biostimulants hold great promise for sustainable crop production and soil health improvement. Future research should focus on low-cost cultivation and harvesting technologies, field scale validation, and standardized product formulations to accelerate the transition toward climate smart and resource sustainable agriculture.